Small businesses and job creation in South Africa - Dhanah, Darlington (Research of GSB, 2018)
There is a paradigm shift from traditionally relying on big businesses for stimulating economic growth and job creation to small businesses in both developed and developing economies. Developing countries in the last 3 decades have accelerated their support for small businesses in a bid to alleviate dire poverty levels they are faced with. Theoretically small businesses are believed to be more labour intensive compared to larger businesses and thus the shift. (Thorsten Beck, Asli Demirguc-Kunt, and Ross Levine, 2003: 2; Beck et al. 2003: 1). Empirically there are ample success stories emanating from China, Pakistan, Brazil just to mention a few, showing a fairly similar trajectory of increased economic participation by small businesses resulting in their significant contribution to GDP and employment creation. However, South Africa has not necessarily followed a similar trajectory to its BRICS counterparts and thus this paper looked at small businesses and job creation in South Africa. It narrowed down to impediments that have stood on the way of small businesses' ability to create jobs. The study was exploratory, descriptive and quantitative in nature. The results to this study are in alignment with previous studies on the subject matter and this study singled out access to finance, HIV Aids, operational costs and government taxes and regulations as statistically significant in explaining variation in the proportion of small businesses that create jobs. This study ultimately recommended that over and above dealing with the above listed impediments directly, government should especially focus on consumer vulnerability and financial conditions on a macro-economic level as these have a direct impact on small businesses.